Modul Penyulutan Inverter Tiga Fasa Menggunakan Bipolar 60 Degrees Pulse Width Modulation - Hidayah, Muhammad Rizki; Mardiyanto, Ignatius Riyadi; Mulyono, Nanang (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
Electrical energy obtained from renewable resources is usually in the form of direct voltage (DC). In comparison, most household and industrial appliances operate using alternating voltage (AC). To connect renewable resources with appliances that require AC, a device that can convert DC voltage to AC is required, known as an inverter. This research focuses on the development of a three phase inverter ignition module with 60 Degrees Pulse Width Modulation (PWM) switching technique. The module uses analog signal processing to adjust the signal and a microcontroller to regulate the voltage generation variables. The work starts from the design stage to the data collection stage of the ignition signal output. The developed module produces six 60-degree PWM signals with a reference frequency of 50 Hz and a carrier frequency of 900 Hz, and a working voltage of 5 volts. The system accuracy was assessed with a reference frequency error of 0.8% and a carrier frequency error of 2.06%.This research shows that the use of the 60-degree PWM technique can result in efficient conversion, making it an effective solution for three-phase inverter applications